A MARKETING BOOKLET: A SOLUTION TO COPE WITH THE UNCLEAR IDENTITY OF HIGH POINT SERVICED APARTMENT SURABAYA - Panca Aditya Pakaya; Jusuf I Ibrahim (Kata Kita: Journal of Language, Literature, and Teaching, 2015)
High Point Serviced Apartment is a serviced apartment established in 2010. As a serviced apartment,many people were confused with the identity of High Point, because its name is a serviced apartment but it operates like a hotel. This problem leads to customer confusion and as a result, the occupancy rate in High Point is pretty low. Therefore, High Pointneeds a marketing booklet which contains company overview, product description, and company address. The company overview which contains brief information about High Point will help to clarify the unclear identity, while the product description which contains detailed information about its products and services will help to promote their products and services. The benefit of thismarketing booklet for High Pointis that it can help to clarifyHigh Point’s identity and can help High Point to get new customers